2000
DOI: 10.1034/j.1600-0757.2000.2220107.x
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of intrabony defects with bone grafts

Abstract: There is substantial clinical and histological evidence that support the concept that extraoral and intraoral autogenous bone grafts and demineralized freeze-dried bone allografts are effective regenerative materials in the treatment of intrabony defects. Moreover, long-term evaluations currently available suggest that the regenerative gains achieved remain clinically stable. Synthetic grafts may result in improved probing depths and clinical attachment levels but have yet to demonstrate the ability to initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 77 publications
5
74
1
4
Order By: Relevance
“…Periodontal regeneration refers to the restoration of supporting tissues of the teeth, which is the alveolar bone, cementum, and periodontal ligament to their original healthy levels before tissue destruction caused by periodontal pathogens has occurred. Histological examination of the newly formed tissues has to be done to establish that the regeneration has occurred (5,11,27). Currently, osseous grafting and guided tissue regeneration (GTR) are the two techniques with the most histological documentation of periodontal regeneration (15).…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal regeneration refers to the restoration of supporting tissues of the teeth, which is the alveolar bone, cementum, and periodontal ligament to their original healthy levels before tissue destruction caused by periodontal pathogens has occurred. Histological examination of the newly formed tissues has to be done to establish that the regeneration has occurred (5,11,27). Currently, osseous grafting and guided tissue regeneration (GTR) are the two techniques with the most histological documentation of periodontal regeneration (15).…”
Section: Introductionmentioning
confidence: 99%
“…Rosen et al have indicated that it was easy to cause loosening (leading to failure) if the fibrous tissue growth wrapped the interface of the bone substitutes after implantation. 27 In our studies, new bone formed in the pores and connected with materials directly. Radiographic observations demonstrated that the grafting and non-lesion area combined as a whole.…”
mentioning
confidence: 99%
“…(TABLE-3 The primary goal of periodontal therapy is to arrest the progression of periodontal disease and maintain the natural dentition for esthetics and function. If periodontal disease results into a loss of the attachment apparatus, attempts are made to regenerate the periodontium to a pre-diseased state (12) . Though periodontal regeneration continues to be the ultimate goal of periodontal therapy, outcome is dependent on multiple factors.…”
Section: Bone Density Fillmentioning
confidence: 99%